Hematological reference values for healthy fat-tailed sheep (Dhumba) in Bangladesh - Islam, Shariful; Rahman, Md Kaisar; Ferdous, Jinnat; Hossain, Muhammad Belal; Hassan, Mohammad Mahmudul; Islam, Ariful (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: There is scarce literature regarding hematology profile of fat-tailed sheep (Dhumba). The study was conducted to determine reference intervals for their hematology profile in the context of Bangladesh. Materials and methods: Blood samples were collected from 32 healthy fat-tailed sheep from Dhaka, Bangladesh, during September–October, 2015. Hemoglobin (Hb), packed cell volume (PCV), erythrocyte sedimentation rate (ESR), total leukocyte count (TLC), total erythrocyte count (TEC), lymphocyte, monocyte, eosinophil, basophil, and neutrophil counts were measured. Results: The levels showed a wide range and variation based on age and sex. Adult sheep had significantly (p = 0.01) higher Hb level than that of juvenile (<6 months of age). Other parameter values were almost similar for both adult and juvenile. The only two hematological parameters, showing noteworthy differences between male and female, were TLC and Basophil level (p < 0.05) in blood. Conclusion: The study sets baseline for future research and diagnosis of diseases in fat-tailed sheep. It also helps for profitable production of fat-tailed sheep in Bangladesh. http://doi.org/10.5455/javar.2018.e302